Compared With Girls, Boys' Psychological Symptoms Are More Likely to Be Influenced by Lifestyle in Chinese Middle School Students - Lu, Jinkui; Tan, Chun; Zhou, Jianfeng; Sha, Mian; Xu, Yongli; Qiu, Jianhua; Liu, Ningling (Frontiers in Psychology, 2022)
Purpose To explore the relationship between Chinese middle school students' lifestyles and psychological symptoms and compare the differences between genders. Method Using the method of stratified cluster sampling, 14,356 students aged 13–18 years from 8 cities in China were selected as participants. The Multidimensional Sub-health Questionnaire of Adolescents was used to estimate psychological symptoms. Chi-square test and Logistic regression analysis were used to analyze the relationship between lifestyle and psychological symptoms. Results The psychological symptom detection rate of Chinese middle school students was 21.37%. The detection rate of psychological symptoms for boys was 22.1%, which was significantly higher than for girls (20.64%, χ2 = 4.608, P < 0.05). According to the Logistic regression analysis, factors that have a positive correlation with the demonstration of psychological symptoms (P < 0.01) include: how the students go to school (by foot or on the vehicle) (OR = 1.16, 95% CI: 1.07–1.25); inadequate time for sleep (OR = 1.48, 95% CI: 1.28–1.72); video watching time ≥2 h/d (OR = 1.25, 95% CI: 1.13–1.39); never exercise (OR = 2.39, 95% CI: 2.07–2.76); never participate in extracurricular exercises (OR = 1.45, 95% CI: 1.27–1.66); have breakfast occasionally (OR = 1.35, 95% CI:1.22–1.50); never have breakfast (OR = 1.90, 95% CI: 1.62–2.24); always have snacks (OR = 1.27, 95% CI: 1.13–1.44); always drink sugared beverages (OR = 1.37, 95% CI: 1.22–1.55); picky with food occasionally (OR = 1.22, 95% CI: 1.11–1.33). Conclusions There was a positive correlation between unhealthy lifestyle and the occurrence of psychological symptoms, and boys are more easily influenced by lifestyles than girls.